Leading Program in Moral Development of Santri Students - Rani Arta Mediana; Purnama Sari; Weti Susanti (Sekolah Tinggi Agama Islam Pengembangan Ilmu Al-Qur`an Sumatera Barat, 2023)
The main problem discussed in this article is how to implement superior programs in madrasas in developing students morals. Several superior programs at madrasas; tahfidz, liqo and dawn lecture programs. The research method in this article is field research using a case study design and descriptive methods. The data sources used in this writing are the head of the madrasah, dormitory supervisors, parents and students. To obtain the desired data, the author used observation, interview and documentation techniques. During the research process, the author still saw several students who violated madrasa rules, such as not observing etiquette in eating and drinking, etiquette towards Islamic boarding school rules, and etiquette towards the opposite sex. Therefore, this research aims to find out how the implementation of the flagship program affects the moral development of students. Based on the research results, the author concludes that the implementation of superior programs in developing students' morals through tahfidzul Quran, fajr lectures, and liqo' which are carried out in madrasas, has been carried out well according to the existing activity schedule.